Test–retest reliability and sensitivity to change of the dimensional anxiety scales for DSM-5. (8th November 2013) - Knappe, Susanne; Klotsche, Jens; Heyde, Franziska; Hiob, Sarah; Siegert, Jens; Hoyer, Jürgen; Strobel, Anja; LeBeau, Richard T.; Craske, Michelle G.; Wittchen, Hans-Ulrich; Beesdo-Baum, Katja
Abstract : Objective: This article reports on the test–retest reliability and sensitivity to change of a set of brief dimensional self-rating questionnaires for social anxiety disorder (SAD-D), specific phobia (SP-D), agoraphobia (AG-D), panic disorder (PD-D), and generalized anxiety disorder (GAD-D), as well as a general cross-cutting anxiety scale (Cross-D), which were developed to supplement categorical diagnoses in the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5). Methods: The German versions of the dimensional anxiety scales were administered to 218 students followed up approximately 2 weeks later (Study 1) and 55 outpatients (23 with anxiety diagnoses) followed-up 1 year later (Study 2). Probable diagnostic status in students was determined by the DIA-X/M-CIDI stem screening-questionnaire (SSQ). In the clinical sample, Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) diagnoses were assessed at Time 1 using the DIA-X/M-CIDI. At Time 2, the patient-version of the Clinical Global Impression—Improvement scale (CGI-I) was applied to assess change. Results: Good psychometric properties, including high test–retest reliability, were found for the dimensional scales except for SP-D. In outpatients, improvement at Time 2 was associated with significant decrease in PD-D, GAD-D, and Cross-D scores. Discussion: Major advantages of the scales include that they are brief, concise, and based on a consistent template to measure the cognitive, physiological, and behavioral symptoms of fear and anxiety. Further replication in larger samples is needed. Given its modest psychometric properties, SP-D needs refinement. Conclusion: Increasing evidence from diverse samples suggests clinical utility of the dimensional anxiety scales.